Bilayer biocomposites of PVOH/WPI/nano‐silica treated with corona discharge. Issue 12 (19th October 2022) - Lara, Bruna Rage Baldone; de Andrade, Paulo Sérgio; de Oliveira, Ana Carolina Salgado; Junior, Mario Guimarães; Matos, Lays Camila; Tonoli, Gustavo Henrique Denzin; Dias, Marali Vilela
Abstract: In order to evaluate the influence of a different assembly of biocomposites of polyvinyl alcohol (PVOH), whey protein isolates (WPI), and nano‐silica (NS), a bilayer film treated with corona discharge was produced through a two‐step lamination. The first layer of PVOH/NS, treated with up to 90 s of discharge, and the second layer of WPI/NS, the bilayer films had their morphology, tensile strength, and water barrier investigated and compared to a single layer PVOH/WPI/NS film. Corona discharge increased the wettability of the first layer, improving the ability to interact with the second layer, thus increasing the adherence between these layers. Films treated with higher times of discharge showed a homogeneous transition between phases, suggesting compatibility, and adherence between layers. At 90 s of corona discharge treatment, bilayer films showed a tensile strength 72% higher than the bilayer film not treated and also 23% more resistant and 7.4 times more ductile than the single‐layer film. The lamination process and corona treatment increase the affinity of water with film constituents, thus leading to a higher permeability. The use of corona discharge associated with the lamination of PVOH/WPI/NS biocomposites provides a bilayer film and produces a more resistant, flexible, and ductile biocomposite film for packaging. Abstract :